Tradition to Technology: The Transformation of Indonesian Culture in the Social Media Era - Muhammad Badad Alauddin; Dynia Fitri; Febby Apri Wenando (MD Research Center, 2025)
This research aims to explore the impact of social media on Indonesian culture through a literature study approach. In the increasingly digital context of Indonesia, social media has a significant influence on various aspects of social, cultural, and economic life. This study highlights both the positive and negative impacts of social media. On the positive side, social media has become an important tool for expressing cultural identity, promoting cultural heritage, and fostering cultural diplomacy. Platforms like Instagram and TikTok provide space for the younger generation in Indonesia to share traditional cultural practices and strengthen pride and attachment to local culture. However, negative impacts also emerge, such as the spread of false information that can lead to social fragmentation, hatred, and discrimination. Additionally, changes in language and communication styles influenced by social media raise concerns about the preservation of more traditional Indonesian languages and cultures. This research also emphasizes the role of social media in marketing and consumer behavior, as well as how it can accelerate the digital divide in Indonesia. The study concludes that while social media offers many benefits, significant challenges in managing its negative effects, such as misinformation and social pressure, must be addressed. This research provides valuable insights into understanding the dynamics of Indonesian culture in the digital era and the importance of a balanced strategy in leveraging social media for social and cultural progress.